Psychometric Validation of the Romanian Version of the Adult Hope Scale (AHS) - Adriana Camelia Neagu; Sorin Ursoniu; Ion Papava; Iuliana-Anamaria Trăilă; Lavinia Palaghian; Catalina Giurgi-Oncu; Ana-Cristina Bredicean (Behavioral Sciences)
The present study aimed to adapt and validate the Adult Hope Scale (AHS) for the Romanian population, addressing a gap in culturally appropriate instruments for measuring dispositional hope. Based on Snyder’s theoretical model, the AHS was translated, culturally adapted, and administered to 663 Romanian adults. Psychometric evaluation included internal consistency (Cronbach’s α = 0.84 for the eight positively worded items), test–retest reliability (ICC = 0.39 for the full scale), exploratory and confirmatory factor analyses, and assessments of convergent and discriminant validity. The two-factor model of the scale (agency and pathways) was confirmed, with significant item loadings and a strong correlation between the two latent factors (r = 0.717). Convergent validity was supported by moderate correlations with the Brief Resilience Scale (r = 0.36–0.45), while discriminant validity was indicated by low correlations with the Trait Anxiety Inventory (r = 0.18–0.20). Demographic analyses revealed higher hope levels in women and engineers, with significant differences by gender (p = 0.00018), education (p = 0.031), and profession (p = 0.008). Despite moderate temporal stability and one weakly performing item, the Romanian AHS demonstrates strong psychometric properties, making it a valid and reliable tool for assessing hope in research and clinical settings.